Thermal Management of Photovoltaic Modules: Material Strategies and Structural Optimization - Wen, Tianhao (Exploring Science Academic Conference Series, 2026)
The industrialization of TOPCon and perovskite-silicon tandem solar cells has shifted photovoltaic thermal management from a one-size-fits-all cooling approach to customized strategies that target specific degradation mechanisms. In these advanced cells, high temperatures induce irrever sible degradation —such as surface passivation degradation in TOPCon and halide ion migration in perovskite tandems—that cannot be reversed by simple temperature reduction. This review synthesizes current understanding of these degradation pathways and evaluates the design principles and durability of radiative cooling coa tings, phase-change materials, and spectrally selective encapsulants. It further examines structural measures —including fractal fins, heat pipes, and array spacing optimization—that enhance heat dissipation. A quantitative framework integrating thermal, electrical, thermodynamic, and economic metrics with levelized cost of electricity (LCOE) is proposed to enable objective comparisons across climates and technologies. We argue that coordinated material–structure design offers the most promising route to overcoming performance bottlenecks and bridging the gap between laboratory breakthroughs and industrial deployment.